Factors influencing household production of sorghum and millet in Kiminini sub-county of Trans-Nzoia county, Kenya (Journal of Sustainability, Environment and Peace, 2019)
The production of sorghum and millet has remained low, and to some extent declined in most regions of Kenya. Little documented information exists on the main causes of this decline and the effects on household income and food security in Kiminini sub-county, and Trans Nzoia County in general. This study therefore sought to identify the factors that influence household production of sorghum and millet in Kiminini Sub-county of Trans-Nzoia County. Specifically, the study examined the extent of production of sorghum and millet; the factors that influence farmers’ preference for other crops; and the impact of such decline to households’ food security. The study utilized a random sample of 100 farm households to collect primary data using a structured questionnaire and an interview schedule. Secondary data were collected from documented information on sorghum and millet production in the study area and the whole country at large. Data were then analyzed using both descriptive and inferential statistics. Data presented in this study reveal the following: First, production of sorghum and millet in Kiminini Location is low and declining. Second, socio-economic characteristics typical of most households especially food prices, education level, gender and cultural values, farm size, off-farm employment, off-farm income, total household income, farm labour supply and number of household dependants, maize preference and the negative attitude towards sorghum and millet cultivation determine sorghum and millet production in the study area. In view of the above findings, this study recommendations that there is need to increase sorghum and millet production by studying the attitudes of the producers, recognizing the important of household governance, particularly the role women play in household food production, involving them in decision-making processes, providing credit facilities and subsidizing prices of farm inputs in order to make them affordable to farmers.
Keywords: Sorghum, Millet, Household governance, food security